The Effect of Supportive Educational Program on Depression, Anxiety, Stress and Satisfaction of the Families of Patients with Acute Coronary Syndrome - Fatemeh Faroujizadeh; Nayyereh Davoudi; Seyyed Reza Mazlom; Melika Ghahramanzadeh; Fateme Hajiabadi (Mashhad University of Medical Sciences, 2023)
Background: Hospitalization in the coronary care unit causes psychological stress for the patient's family members. Education and support of these families may control depression, anxiety and stress and increase their satisfaction.Aim: This study was performed with aim to determine the effect of the supportive educational program on depression, anxiety and stress and satisfaction of the families of patients admitted to the coronary care unit. Method: This randomized clinical trial study was performed in 2019 on 70 families of patients with acute coronary syndrome hospitalized in the coronary care unit of Imam Reza and Ghaem hospitals in Mashhad. Patients' families were randomly assigned to the intervention and control groups by time block method. In the intervention group, the supportive educational program was implemented for three days and the control group received routine care. Depression, anxiety and stress scale (DASS) was completed in both groups before and after the intervention, and the questionnaire of the Family Satisfaction with Care in the Intensive Care Unit (FS-ICU) was also completed after the intervention. Data were analyzed by SPSS (version 16).Results: After the intervention, the mean total score of depression, anxiety and stress of the patients' families in the intervention group was significantly lower than the control group (P<0.001). Also, the total score of depression, anxiety and stress after the intervention was reduced compared to before the intervention in the intervention group and also in the control group (P<0.001). Also, the mean satisfaction score of patients' families in the intervention group was significantly higher than the control group (P<0.001).Implications for Practice: Based on the findings of this research, the supportive educational program reduced depression, anxiety and stress in the families of patients with acute coronary syndrome hospitalized in the coronary care unit and increased their satisfaction.